Evaluation of the processing of sensory processes in the process of neurodevelopment treatment - Habik-Tatarowska, Natalia (Journal of Education, Health and Sport, 2019)
The proper development of sensorimotor integration depends on the efficient functioning of the central nervous system and on the inflow of the right amount of stimuli from your own body and from the environment. Integration of information from basic sensory systems - vestibular, proprioceptive and tactile - plays a particularly important role here. Appropriate stimulation of the nervous system by stimuli derived from the three basic senses is essential for proper psychomotor development of the infant. The high plasticity of the ripening central nervous system means that early treatment may cause the alleviation or even withdrawal of pathological symptoms. The aim of the study is to assess the level of sensory integration in children with locomotive motor disorders and to assess the possibility of stimulation of this process during NDT-Bobath therapy.The research included 43 children aged 4-12 months in the Świętokrzyskie Province. The tests used the Sensomotor Functions Test in Infants (TSFI), which were carried out twice (before the rehabilitation and after four months of therapy). Before starting the rehabilitation, 81% of the children experienced impaired processing of sensory integration processes. After four months, this percentage decreased to 47%. The most significant changes were found in the field of touch and vestibular integration. Disturbances in the processing of sensory integration processes are a significant problem in children with motor-related disorders of central origin. The NDT-Bobath method improves the functioning of sensory processes.